Smallpox: An eradicated infection with persistent sequels – Case report and a brief on smallpox - Jastaneiah, Sabah (Elsevier, 2009)
Sequelae of smallpox infection on the ocular surface are still seen, including corneal scars adherent leukoma and phthisical globes. This paper will report another sequel of smallpox infection causing inadvertent bleb in a 62-year-old diabetic female with no history of ocular surgery or trauma in either eye. The patient had smallpox infection during her childhood. Her follow up extended from May 1997 until August 2007 with a constant eye examinations including controlled intraocular pressure, avascular cystic inadvertent bleb, and up drown peaked pupil.